FIB-induced dislocations in Al submicron pillars: Annihilation by thermal annealing and effects on deformation behavior. (15th May 2016) - Lee, Subin; Jeong, Jiwon; Kim, Youbin; Han, Seung Min; Kiener, Daniel; Oh, Sang Ho
Abstract: In-situ transmission electron microscopy (TEM) annealing of submicron Al pillars (∼300–450 nm in diameter) fabricated by focused ion beam (FIB) shows that the dislocation loops formed by the high energy Ga + ion beam impact near the material surface can be removed by annealing at around half of the melting point ( T m ). Quantitative analysis of real-time TEM data reveals that the dislocation loops first show a ripening behavior at around 0.4 T m, i.e. larger loops coarsen at the expense of smaller ones. Subsequently, the ripened loops start to shrink and are eventually annihilated at ∼0.5 T m by the diffusion of thermally activated vacancies. Microcompression tests on the as-fabricated and annealed pillars suggest that the FIB-induced defects, particularly dislocation loops, distinctively affect the deformation behavior of submicron Al pillars; while the yield and flow stresses appear unaffected by the annealing, strain bursts are larger and more frequent in the annealed pillars compared to those of as-fabricated samples. In-situ TEM compression revealed that the initial plastic deformation and subsequent plastic flow of Al pillars are significantly altered by the presence of FIB-induced dislocation loops, as they actively respond to the applied stress. We observe that the initial dislocation activity in most FIB-prepared pillars was the glide of FIB-induced dislocation loops. With further straining, the dislocation loops escaped the pillar, leaving slip steps at the pillar surface and/or dislocation debris within the pillar volume via the interaction with other mobile dislocations. The subsequent dislocation slip is mostly localized at these locations, thereby forming large slip steps. Contrarily, in the case of annealed pillars, the deformation was rather homogeneous with the formation of multiple fine slip steps. The present direct TEM observations contribute to the understanding of the nature of FIB-induced defects and reveal their distinct roles in the deformation behaviors of submicron pillars. Graphical abstract: